2014
DOI: 10.1186/1556-276x-9-498
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism and optical properties of La1 − xAl x FeO3 nanopowders

Abstract: La1 − x Al x FeO3 (x = 0.0, 0.05, 0.1, 0.2, 0.3, 0.4, and 0.5) nanopowders were prepared by polymerization complex method. All prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), and UV-vis spectrophotometry (UV-vis). The magnetic properties were investigated using a vibrating sample magnetometer (VSM). The X-ray results of all samples show the formation of an orthorhombic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…nanoparticles obtained by us is higher whereas H c is lower than Zn doped LaFeO 3 synthesized by co-precipitation method as reported by Mukhopadhyay et al [49]. Similarly, Yutana et al [36] studied the enhancement of magnetic properties of LaFeO 3 synthesized by polymerizationcomplex method at higher doping of Al (x=0.5) and the M s (1.66 emu/g) is comparable with our result at lower doping of Ce. Thus, it has been observed that the nature of doped metal ion and choice of synthetic route can significantly affect the magnetic parameters of nanomaterials.…”
Section: Mӧssbauer Analysissupporting
confidence: 92%
“…nanoparticles obtained by us is higher whereas H c is lower than Zn doped LaFeO 3 synthesized by co-precipitation method as reported by Mukhopadhyay et al [49]. Similarly, Yutana et al [36] studied the enhancement of magnetic properties of LaFeO 3 synthesized by polymerizationcomplex method at higher doping of Al (x=0.5) and the M s (1.66 emu/g) is comparable with our result at lower doping of Ce. Thus, it has been observed that the nature of doped metal ion and choice of synthetic route can significantly affect the magnetic parameters of nanomaterials.…”
Section: Mӧssbauer Analysissupporting
confidence: 92%
“…All samples exhibit similar absorption bands around 579–602 cm −1 , which can be attributed to the Fe-O stretching vibration ( Figure 1 a,b), confirming magnetite presence [ 35 , 36 , 37 ]. In addition, weak absorption bands are observed at 1628 cm −1 ( Figure 1 a), in the case of samples prepared at 100 °C (S1–S3), which could be attributed to the bending mode of O-H bond or to the carbonate groups from atmospheric CO 2 [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 65%
“…The experimentally assessed direct energy band gaps of all perovskite nanomaterials are 1.15, 1.31, 1.34 and 1.32 eV for LaMnO 3 , La 0.95 Ce 0.05 MnO 3 , La 0.93 Ce 0.07 MnO 3 , and La 0.90 Ce 0.10 MnO 3 perovskites, respectively. An observed increase band gap energy with increasing the Ce 3+ ion substitution quantity into the LaMnO 3 crystal lattice, which is attributable to the Burstein-Moss effect 28,30–32 .
Figure 5( a) UV/Vis absorption spectra and ( b ) The plot of (αh ν ) 2 vs. photon energy(h ν ) LaMnO 3 , La 0.95 Ce 0.05 MnO 3 , La 0.93 Ce 0.07 MnO 3 and La 0.90 Ce 0.10 MnO 3 nanoparticles.
…”
Section: Resultsmentioning
confidence: 96%